Dimethyl Sulfoxide Enhances Kaposi’s Sarcoma-Associated Herpesvirus Production During Lytic Replication - Kang, Su-Kyung; Lee, Myung-Ju; Ryu, Ho-Hyun; Lee, Jisu; Lee, Myung-Shin (Frontiers in Microbiology, 2021)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is an etiologic agent of Kaposi’s sarcoma, primary effusion lymphoma, and multicentric Castleman disease. In studies of KSHV, efficient virus production and isolation are essential. Reactivation of KSHV can be initiated by treating latently infected cells with chemicals, such as 12-O-tetradecanoyl-phorbol-13-acetate and sodium butyrate. These chemicals have been used as tools to induce lytic replication and viral production in KSHV-producing cell lines. Dimethyl sulfoxide (DMSO) is an organosulfur compound that is frequently used as an aprotic solvent similar to water. In experiments exploring signaling pathways in KSHV-infected cells, DMSO treatment alone as a vehicle affected the lytic gene expression of KSHV. However, to the best of our knowledge, the effects of DMSO on KSHV-producing cells have not yet been reported. Therefore, in this study, we investigated whether DMSO could be used as a reagent to enhance viral production during lytic replication in KSHV-producing cells and assessed the underlying mechanisms. The effects of DMSO on KSHV production were analyzed in iSLK BAC16 cells, which have been widely used for recombinant KSHV production. We found that the production of KSHV virions was significantly increased by treatment with DMSO during the induction of lytic replication. Mechanistically, lytic genes of KSHV were enhanced by DMSO treatment, which was correlated with virion production. Additionally, DMSO induced the phosphorylation of JNK during lytic replication, and inhibition of JNK abolished the effects of DMSO on lytic replication and virion production. Our findings showed that additional treatment with DMSO during the induction of lytic replication significantly improved the yield of KSHV production.